What are undergraduate students' perceptions of a peer coaching model intended to foster effective electronic communication strategies with parents?. Issue 1 (2nd January 2021) - Macy, Marisa; Spinetti Rincón, María Paola; Hogan, Melissa
ABSTRACT: Effective parental communication is a professional responsibility that is often overlooked in preparing the next generation of early childhood educators. Preparation programs that incorporate context-embedded opportunities for preservice professionals to be involved with parents are needed. This study examined a personnel preparation model which incorporated peer coaching to develop effective electronic communication skills. Students in a university course communicated assessment information using an electronic format as an alternative to face-to-face interactions. Students received feedback from peer coaches on their electronic communication a total of six times during the semester. To target diverse populations, one of the peer coaches was a non-native English speaker. After an entire semester of peer-coaching, students completed a survey regarding the program and their views on the efficacy of the peer coaching model. Results indicated that students perceived the program to provide relevant experiences and opportunities to improve their electronic communication skills with families. Participants stated the need for further context-embedded instances in which they could interact with families with diverse backgrounds in the preparation program.